2019
DOI: 10.1186/s13007-019-0435-7
|View full text |Cite
|
Sign up to set email alerts
|

PGA: a software package for rapid, accurate, and flexible batch annotation of plastomes

Abstract: Background Plastome (plastid genome) sequences provide valuable information for understanding the phylogenetic relationships and evolutionary history of plants. Although the rapid development of high-throughput sequencing technology has led to an explosion of plastome sequences, annotation remains a significant bottleneck for plastomes. User-friendly batch annotation of multiple plastomes is an urgent need. Results We introduce Plastid Genome Annotator (PGA), a standalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
697
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 811 publications
(699 citation statements)
references
References 19 publications
2
697
0
Order By: Relevance
“…DNA data were sequenced using the Illumina Hiseq 2500 platform (Illumina, San Diego, CA, USA). Subsequently, chloroplast genome assembly using GetOrganelle (Jin et al 2018) and the annotation was performed with PGA (Qu et al 2019), then confirmed manually. Finally, the complete chloroplast genome was deposited in GenBank (accessible numbers: MT021458 and MT021459).…”
Section: Anoectochilus Nandanensis; a Calcareus; Chloroplast Genome;mentioning
confidence: 99%
“…DNA data were sequenced using the Illumina Hiseq 2500 platform (Illumina, San Diego, CA, USA). Subsequently, chloroplast genome assembly using GetOrganelle (Jin et al 2018) and the annotation was performed with PGA (Qu et al 2019), then confirmed manually. Finally, the complete chloroplast genome was deposited in GenBank (accessible numbers: MT021458 and MT021459).…”
Section: Anoectochilus Nandanensis; a Calcareus; Chloroplast Genome;mentioning
confidence: 99%
“…In this pipeline, the complete cp genome reads were extracted from total genomic reads and were subsequently assembled using SPAdes version 3.10 (Bankevich et al 2012). The genes were annotated using PGA (Qu et al 2019) and Geneious 11.0.3 (Kearse et al 2012) with the published complete cp genome of E. lishihchenii (GenBank accession number: NC_029944) as the reference. Transfer RNAs (tRNAs) were confirmed by their specific structure predicted by tRNAscan-SE 2.0 (Lowe and Chan 2016).…”
mentioning
confidence: 99%
“…Plastome assembly was performed with Organelle Genome Assembler (OGA) as described in Qu, Fan, et al (2019). Plastome annotation was performed with Plastid Genome Annotator (PGA) (Qu, Moore, et al 2019), with manual correction with Geneious v9.1.4. The annotated complete plastome was submitted to GenBank under accession number MT083894.…”
mentioning
confidence: 99%